Elevated Th22 cells and related cytokines in patients with epithelial ovarian cancer. Issue 43 (October 2017) - Wang, Ting; Zhang, Zhiwei; Xing, Huaixin; Wang, Li; Zhang, Guoxiang; Yu, Na; Wang, Junzhi; Guo, Wei; Jiang, Jie
Abstract : Abstract: This study is conducted to investigate the involvement of T-helper (Th) cells and regulatory T cells in epithelial ovarian cancer (EOC). The percentages of Th22, Th17, Th1, and regulatory T cells in the peripheral blood of EOC patients, benign ovarian epithelial neoplasm (BOEN) patients, and healthy control (HC) were examined by flow cytometry. Enzyme-linked immunosorbent assay was used to determine serum levels of interleukin (IL)-22, IL-17, interferon-γ (IFN-γ), and tumor necrosis factor-α (TNF-α). Th22 and Th17 were significantly increased in EOC patients. The plasma concentrations of IL-22 and TNF-α were significantly elevated in EOC patients compared with BOEN patients and HC. In EOC patients, there was an increased trend of Th22, IL-22, and TNF-α in stage III–IV patients compared with stage I–II patients. A positive correlation was seen among Th22, Th17, and Th1 cells in EOC patients. Similarly, positive correlations were detected between Th22 cells and IL-22 or TNF-α and between Th1 cells and interferon-γ (IFN-γ) in EOC patients. Besides, no significant difference was found in Th1 cells and regulatory T cells among EOC and BOEN patients and HC. There is a higher circulating frequency of Th22, Th17 cells, IL-22, and TNF-α concentration in EOC patients, which may conjointly participate in the pathogenesis and growth of EOC. Abstract : Supplemental Digital Content is available in the text